Low-molecular-weight-heparin can benefit women with recurrent pregnancy loss and sole protein S deficiency: a historical control cohort study from Taiwan. Issue 1 (December 2016) - Shen, Ming-Ching; Wu, Wan-Ju; Cheng, Po-Jen; Ma, Gwo-Chin; Li, Wen-Chu; Liou, Jui-Der; Chang, Cheng-Shyong; Lin, Wen-Hsiang; Chen, Ming
Abstract Background Heritable thrombophilias are assumed important etiologies for recurrent pregnancy loss. Unlike in the Caucasian populations, protein S and protein C deficiencies, instead of Factor V Lieden and Prothrombin mutations, are relatively common in the Han Chinese population. In this study we aimed to investigate the therapeutic effect of low molecular weight heparin upon women with recurrent pregnancy loss and documented protein S deficiency. Methods During 2011–2016, 68 women with recurrent pregnancy loss (RPL) and protein S deficiency (both the free antigen and function of protein S were reduced) were initially enrolled. All the women must have experienced at least three recurrent miscarriages. After excluding those carrying balanced translocation, medical condition such as diabetes mellitus, chronic hypertension, and autoimmune disorders (including systemic lupus erythematosus and anti-phospholipid syndrome), coexisting thrombophilias other than persistent protein S deficiency (including transient low protein S level, protein C deficiency, and antithrombin III), only 51 women with RPL and sole protein S deficiency were enrolled. Initially they were prescribed low dose Aspirin (ASA: 100 mg/day) and unfortunately there were still 39 women ended up again with early pregnancy loss (12 livebirths were achieved though). Low-molecular-weight-heparin (LMWH) was given for the 39 women in a dose of 1 mg/Kg every 12 h from the day when the next clinical pregnancy was confirmed to the timing at least 24 h before delivery. The perinatal outcomes were assessed. Results Of 50 treatment subjects performed for the 39 women (i.e. 11 women enrolled twice for two pregnancies), 46 singletons and one twin achieved livebirths. The successful live-birth rate in the whole series was 94 % (47/50). Nineteen livebirths delivered vaginally whereas 28 delivered by cesarean section. The cesarean delivery rate is thus 59.57 %. Emergent deliveries occurred in 3 but no postpartum hemorrhage had been noted. Conclusions Our pilot study in Taiwan, an East Asian population, indicated anti-coagulation therapy is of benefit to women with recurrent pregnancy loss who had documented sole protein S deficiency. Trial registration ISRCTN64574169 . Retrospectively registered 29 Jun 2016.